Gambaran Pertumbuhan Kepesertaan Jaminan Kesehatan Nasional Berdasarkan Provinsi di Indonesia: Overview of National Health Insurance Participation Growth by Province in Indonesia - Gulo, Estika Putri Cahayani (Dohara POAJ, 2025)
Introduction: National Health Insurance is one of the policies to support the implementation of social development programs in Indonesia. The purpose of this study is to identify the Growth Overview of National Health Insurance Membership based on Provinces in Indonesia. Methods: This research design uses a descriptive research design. The data source in this study is a secondary data source. The study uses univariate analysis to describe the picture of the variables studied. Results: Based on data on active and inactive participants in the National Health Insurance it is known that the number of active participants has increased from 2017-2018 by 0,11% and 2018-2019 an increase of 0,08%; in 2019-2020 there was a decrease of 0,01% and 2020-2021 the number of active participants rose again by 0,02%. Discussion: Based on data from active and inactive National Health Insurance participants it is known that the number of active participants has increased from 2017-2019, in 2020 and 2021 the number of active participants has decreased. Meanwhile, inactive participants have increased every year namely from 2017-2021.